0
$\begingroup$

I have been given this statement to convert to CNF:

$$((a \to x) \land (b \to c)) \to (a \to ¬c)$$

and so far I have gotten rid of the implications and applied de Morgan's law after which I have:

$$((a \land \lnot x) \lor (b \land \lnot c)) \lor (\lnot a\lor \lnot c)$$

but I can't figure out how to proceed from this point and how I would apply distributivity laws on this.

$\endgroup$
0
$\begingroup$

Let X, Y, Z be three propositions ( either atomic, or compound,we needn't care):

Distributivity of OR over & means that :

X OR ( Y & Z) is equivalent to (X OR Y) & ( X OR Z).

Any thing , any proposition ( either atomic or compound) can play the role of X, Y or Y.

So, here:

Let (a&~x) play the role of X.

Let b play the role of Y.

Let ~c play the role of Z.

Further transformations may require you to let other propositions play the roles of X, Y and Z.

Maybe, after having applied distributivity once, you'll have to use OR-commutativity in order to be in a position to apply distributivity a second time.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.